EMU and capital markets: The institutional framework - Daniel Gros (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
This paper reviews the factors that will determine the shape of financial markets under EMU. It argues that financial markets will not be unified by the introduction of the euro. National central banks have a vested interest in preserving local idiosyncracies (e.g. the Wechsels in Germany) and they might be allowed to do so by promoting the use of so-called tier two assets under the common monetary policy. Moreover, a host of national regulations (prudential and fiscal) will make assets expressed in euro imperfect substitutes across borders. Prudential control will also continue to be handled differently from country to country. In the long run these national idiosyncracies cannot survive competitive pressures in the euro area. The year 1999 will thus see the beginning of a process of unification of financial markets that will be irresistible in the long run, but might still take some time to complete.
urn:nbn:de:hebis:30-9294
Keywords: E58; G19; 330; European Central Bank; Financial Market Structure; EMU